2011
DOI: 10.1021/jp208998j
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic Properties of Strained Pd Nanoshells at Au Nanostructures: CO and HCOOH Oxidation

Abstract: The oxidations of carbon monoxide and formic acid at ultrathin Pd layers grown on Au nanoparticles were studied as a function of Pd thickness. Pd shells with thickness between 1 and 10 nm were grown on 19 nm Au nanoparticles by chemical reduction of H 2 PdCl 4 with ascorbic acid. High-resolution transmission electron microscopy and X-ray diffraction confirm the coreÀshell configuration of the nanostructures. While the synthesis of pure Pd nanostructures led to a rather amorphous material, Pd nanoshells exhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
63
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(72 citation statements)
references
References 50 publications
9
63
0
Order By: Relevance
“…Kolb et al demonstrated that the electrocatalytic activity of Pd overlayers on Au and Pt single crystal electrodes depends markedly on their crystallographic orientation; following the trend Pd(111) < Pd(110) < Pd(100) [15,16]. Although in previous studies the same authors showed that the activity of Pd nanostructures towards HCOOH oxidation is enhanced in the presence of a carbon support, leading to lower deactivation kinetics under potentiostatic conditions [13,14,17];…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kolb et al demonstrated that the electrocatalytic activity of Pd overlayers on Au and Pt single crystal electrodes depends markedly on their crystallographic orientation; following the trend Pd(111) < Pd(110) < Pd(100) [15,16]. Although in previous studies the same authors showed that the activity of Pd nanostructures towards HCOOH oxidation is enhanced in the presence of a carbon support, leading to lower deactivation kinetics under potentiostatic conditions [13,14,17];…”
Section: Introductionmentioning
confidence: 99%
“…The electrooxidation of HCOOH on Pd nanostructures has been widely investigated in the literature [7][8][9][10][11][12][13][14]. Kolb et al demonstrated that the electrocatalytic activity of Pd overlayers on Au and Pt single crystal electrodes depends markedly on their crystallographic orientation; following the trend Pd(111) < Pd(110) < Pd(100) [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…In catalysis, bimetallic core-shell nanoparticles have raised a lot of interest in different fields due to their enhanced properties compared to their monometallic counterparts [4-6]. The electronic structure of the surface atoms can be tuned by changing of core and shell metals thereby tuning their chemical and physical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Both, epitaxial and non-epitaxial shells have been synthesized for different applications [9-13]; however, epitaxial growth has not been thoroughly investigated in core-shell nanoparticles. Several works have studied the effect of elastic strain in the catalytic activity of metal films [14-17] and core-shell nanoparticles [4, 6, 18-22] as well as a substrate for surface-enhanced Raman scattering [23]. Therefore, it is necessary to study in detail the interface of these heterostructures to understand the growth of the shell and the appearance of defects that will alter the properties of such materials.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of the reactivity of nanoparticles as catalysts for electrochemical reactions involve the adsorption or growth of nanomaterials onto solid substrates, e.g. carbon materials [19,20], oxide materials [21], metal substrates [22] or molecular templates [23], which allow formation of an electronic contact required to control electrochemical reactions. The potential is then applied through the substrate material.…”
Section: Introductionmentioning
confidence: 99%